The Impact of Good Agriculture Practices (GAP) Implementation on Productivity of Pacific White Shrimp in Grabag District Purworejo Regency - Asyifa Anandya; Jamhari Jamhari; Suhatmini Hardyastuti (Agro Ekonomi, 2018)
Purworejo Regency is one of the centers of pacific white shrimp cultivation in Indonesia. One of the sub-districts in Purworejo Regency which successfully cultivates the pacific white shrimp is Grabag Sub District, who won the first place of shrimp cultivation competition in organization and institution performace assessment category for Central Java Province level and national first place winner in shrimp cultivation category. This research was located in the sub district of Grabag, Purworejo regency on October 2017-December 2017. The aims of this research are to determine the effect of human capital on the GAP implementation by the farmers and the effect of the GAP implementation on pacific white shrimp productivity. The number of respondents in this research was 75 farmers which were chosen by purposive sampling. This research used regression analysis with Two Stage Least Square model. The results of this research showed that (1) The GAP implementation was influenced by the level of education and farmers’ experiences, while there was no any effect influenced by the age on the GAP implementation, and (2) The GAP implementation of pacific white shrimp cultivation did not affect the pacific white shrimp productivity. However, the GAP implementation did not contradict the productivity. The environmentally friendly GAP implementation and quality oriented did not contradict the productivity of shrimp. Farmers still can implement the GAP without decreasing their productivity.